2009
DOI: 10.2353/ajpath.2009.080055
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Deficiency Is Fully Penetrant for Prostate Adenocarcinoma in C57BL/6 Mice via mTOR-Dependent Growth

Abstract: The tumor suppressor phosphatase and tensin homolog (PTEN) is frequently involved in human prostate carcinoma. PTEN is therefore an attractive target for the development of preclinical animal models. Prostate intraepithelial neoplasia lesions develop in mice with Pten heterozygosity, but disease progression has been reported only in combination with either other tumor suppressor gene alterations or the conditional inactivation of both Pten alleles in prostate epithelial cells. We report that on a C57BL/6 backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
3
36
1
Order By: Relevance
“…8,9 Moreover, PTEN-negative tumors are resistant to androgen deprivation but exhibit enhanced sensitivity to treatments with PI3 kinase and mTORC1 inhibitors, thereby demonstrating a dependency for the mTORC1 pathway for growth in conditions of low androgen circulating levels. [8][9][10] Similar findings have been observed using the human LNCaP xenograft model, 11 which respond better to a combined treatment of castration and rapamycin than to the each of the treatments alone. 12 In contrast to these findings, phase II clinical trials have shown little effects of the rapamycin analogue RAD001 as an addon therapy to the AR antagonist bicalutamide for the treatment of castration-resistant prostate tumors in human patients.…”
Section: Introductionsupporting
confidence: 82%
“…8,9 Moreover, PTEN-negative tumors are resistant to androgen deprivation but exhibit enhanced sensitivity to treatments with PI3 kinase and mTORC1 inhibitors, thereby demonstrating a dependency for the mTORC1 pathway for growth in conditions of low androgen circulating levels. [8][9][10] Similar findings have been observed using the human LNCaP xenograft model, 11 which respond better to a combined treatment of castration and rapamycin than to the each of the treatments alone. 12 In contrast to these findings, phase II clinical trials have shown little effects of the rapamycin analogue RAD001 as an addon therapy to the AR antagonist bicalutamide for the treatment of castration-resistant prostate tumors in human patients.…”
Section: Introductionsupporting
confidence: 82%
“…10 PTEN deficiency is capable of promoting hyperactivation of mTOR in animal models and patients. 11,12 It is widely conceived that mTOR orchestrates cardiac hypertrophy given its role in governing protein synthesis. 13 Aberrant activation of mTOR has been shown to contribute to the onset and development of cardiac hypertrophy.…”
mentioning
confidence: 99%
“…Rapamycin (1.5 mg/100 mL caboxymethyl cellulose) was injected at 0.3 mg/kg on the first day after DMBA implantation and then 0.15 mg/kg every other day for 1 month. This low dose of rapamycin used was selected to minimize potential nonspecific effect and was based on several articles that used a similar protocol (33)(34)(35).…”
Section: Mice and Genotypingmentioning
confidence: 99%